OPTN/SRTR 2018 Annual Data Report: Heart. (2nd January 2020) - Colvin, M.; Smith, J. M.; Hadley, N.; Skeans, M. A.; Uccellini, K.; Goff, R.; Foutz, J.; Israni, A. K.; Snyder, J. J.; Kasiske, B. L.
Abstract: The new adult heart allocation policy was approved in 2016 and implemented in October 2018, so its effect was not yet evident in 2018 data. However, the more granular data being collected are anticipated to allow for improved analyses. In 2018, new listings continued to increase; 3883 new adult and 685 new pediatric candidates were added. In 2018, 3440 heart transplants were performed, an increase of 167 over 2017; 473 transplants occurred in pediatric recipients and 2967 in adult recipients. Short‐term and long‐term posttransplant mortality improved. Overall 1‐year survival for adults who underwent heart transplant in 2011‐2013 was 90.3%, 3‐year survival was 84.7%, and 5‐year survival was 79.6%. Mortality rates for pediatric recipients were 4.5% at 6 months and in 5.9% at 1 year posttransplant, 12.5% at 3 years for transplants in 2014‐2015, 14.8% at 5 years for transplants in 2012‐2013, and 29.8% at 10 years for transplants performed in 2008‐2009.